The Effect of Special Exercises For Developing motor Abilities On Squash Player’s Speed - Jihad, Ali (Journal of Physical Education, 2016)
The problem of the research lies in the slow movement of squash players inside the court and some motor abilities in young squash league players aged 15 – 17 years old. The importance of the research lies in preparing special exercises to develop some motor abilities and identifying their effect on the players speed inside the court. The aims of the research were preparing special exercises for developing motor abilities of young squash players aged 15 – 17 years old as well as identifying the effect of special exercises on the speed of player’s movement in the court. The researchers hypothesized significant differences between pre and posttests in favor of the posttests in some motor abilities of young squash players in addition to that they hypothesized significant differences between pre and posttests in favor of posttests in the speed of player’s movement. The researchers used the experimental method. The subject was selected and the pretests were applied followed by the program then the posttests. The data was collected and treated using SPSS. The researchers concluded that the used exercises developed some motor abilities as well as the motor speed of squash players. Finally they recommended using these special exercises to develop motor abilities in squash players